2019
DOI: 10.14569/ijacsa.2019.0100371
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear EH Relaying in Delay-Transmission Mode over n-µ Fading Channels

Abstract: Energy harvesting is a technique to harvest energy from RF (radio frequency) waves. The RF signals have the ability to convey energy and information concurrently. The EH in cooperative relaying systems may increase the capacity and coverage of wireless networks. In this work, we study a dual-hop (two-hop) relaying. This system has three nodes: a source, a relay, and a destination. The source and destination have multiple antennas. We account a non-linear EH model and TSR (time-switchingbased relaying) protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Chen [23] analyzed the outage probability and throughput of AF systems for energy harvesting under the interference of relay and destination nodes. Hussain et al [24] studied the performance of a two-hop model system with multiple antennas in a κ-µ shadow fading channel. Badarneh et al [25] showed the performance of energy harvesting DF systems in generalized η-µ and κ-µ mixed fading environments with multiple nodes cooperation.…”
Section: B Related Workmentioning
confidence: 99%
“…Chen [23] analyzed the outage probability and throughput of AF systems for energy harvesting under the interference of relay and destination nodes. Hussain et al [24] studied the performance of a two-hop model system with multiple antennas in a κ-µ shadow fading channel. Badarneh et al [25] showed the performance of energy harvesting DF systems in generalized η-µ and κ-µ mixed fading environments with multiple nodes cooperation.…”
Section: B Related Workmentioning
confidence: 99%
“…Generalized − , − , and − shadowed fading models are considered in [29][30][31][32][33] to examine the performance of WP relay systems with EH at the relay node(s). To the best of our knowledge, no work on WP relay systems with EH at source node under consideration of the generalized fading models is reported in the literature.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Integrating a dual-hop relaying system with wireless energy harvesting techniques can enhance the coverage capacity and network life-time [2], [3]. In a dual-hop wireless energy harvesting relaying network, the relay is an energy constrained device which harvests the energy through RF signals [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a dual-hop wireless energy harvesting relaying network, the relay is an energy constrained device which harvests the energy through RF signals [4]. One of the well-known relaying methods is a decode-andforward (DF) relaying, in which relay decodes and sends the information to the destination [2]- [4]. Several authors have investigated the wireless energy harvesting in a DF relaying system [2]- [5], [7]- [13] (and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation